The Relevance of Character Education Values in Ta’līm al-Muta’allim by Imām al-Zarnūjī to the Moral Challenges of Modern Students - Mhd. Husnul Fikri; Eva Dewi; Ummi Mutiah (Bulletin of Indonesian Islamic Studies, 2025)
Education plays a vital role in shaping human character, especially in facing the challenges of the Industrial Revolution 4.0 and the digital era. In Islam, education is not only a means of intellectual development but also a spiritual and moral process aimed at producing insan kamil—a complete human being. One of the classical Islamic literatures that emphasizes the importance of character education is Ta’līm al-Muta’allim by Imām al-Zarnūjī. This research aims to explore the relevance of the character values contained in Ta’līm al-Muta’allim in addressing the moral challenges faced by students in modern times. Using a qualitative library research method, this study analyzes classical texts and relevant contemporary literature. The findings show that the values of sincerity, discipline, respect for teachers, time management, and humility in seeking knowledge are still highly relevant in today's educational context. These values serve as a foundation for developing strong moral character among students, which is essential in responding to the complexities of modern life and preserving ethical behavior amidst technological advancement. This study contributes to the discourse on Islamic character education and offers insights for reforming modern education by integrating classical values.